Against the Environment. Problems in Society/Nature Relations - Aldeia, João; Alves, Fátima (Frontiers in Sociology, 2019)
The dominant manners in which environmental issues have been framed by sociology are deeply problematic. Environmental sociology is still firmly rooted in the Cartesian separation of Society and Nature. This separation is one of the epistemic foundations of Western modernity – one which is inextricably linked to its capitalist, colonial, and patriarchal dimensions. This societal model reifies both humanity and nature as entities that exist in an undeniably anthropocentric cosmos in which the former is the only true actor. Anthropos makes himself and the world around him. He conquers, masters, and appropriates the non-human, turning it into the mere environment of his existence, there solely for his use. If sociology remains trapped in this paradigm it continues to be blind to the multiple space-time specific interrelations of life-elements through which heterogeneous and contingent ontologies of humans and extra-humans are enacted. If these processes of interconnection are not given due attention, the socioecological worlds in which we – human as well as others – live cannot be adequately understood. But misunderstandings are not the only issue at stake. When dealing with life-or-death phenomena such as climate change, to remain trapped inside the Society/Nature divide is to be fundamentally unable to contribute to world reenactments that do not oppress – or, potentially, extinguish – life, both human and extra-human. From the inside of Anthropos’ relation to his environment the only way of conceiving current socioecological problems is by framing them in terms of an environmental crisis which could, hypothetically, be solved by the very same societal model that created it. But if the transformation of some of the world(s)’ life-elements into the environment of the Human is part of the problem, then, socioecological issues cannot be adequately understood or addressed if they are framed as an environmental crisis. Instead, these problems need to be conceived as a crisis of Western modernity itself and of the kind of worlds that are possible and impossible to build within it.